Pengaruh Beban Kerja Dan Stress Kerja Terhadap Kinerja Perawat Di Rumah Sakit Bhayangkara Setukpa Lemdiklat Polri Sukabumi - Davi Sundari; Ellina Ellina (Publikasi Indonesia, 2022)
Performance is highly correlated with workload and work stress for nurses providing health care, with higher workload and work stress associated with lower performance. This study aims to identify and analyze the relationship between workload and work stress in nurses at the Sukabumi Police Job Training Center, Bhayangkara Setukpa Hospital. The research design adopted a quantitative analysis survey with a cross-sectional design. There were 80 nurses working in the inpatient ward of Remdikrat Police Training Center Sukabumi RS Bayankara Setukpa. The sampling technique used was proportional random sampling. The sample size was 68 nurses. Data were analyzed using univariate, bivariate and multivariate chi-square analysis. The results for workload variables obtained p-value = 0.000, work stress 0.001 <0.05 which indicates that workload and work stress affect nurse performance. B 7.017 indicates that workload affects nurse performance by a factor of 7. Workload and work stress affect nurse performance. Multivariate analysis revealed that the main result was the effect of workload on nurses' performance. Nurses are advised to spend more time on the tasks assigned to them and hospitals need to improve their policies to improve nurses' performance. For nurses, coaching and training policies can improve nurses' performance. Further investigation is recommended.